Lipase-catalyzed synthesis of sucrose monoester: Increased productivity by combining enzyme pretreatment and non-aqueous biphasic medium - Pranee Inprakhon (2018)
© 2017 Elsevier B.V. Sucrose monocaprate was synthesized by carrying out a lipase-catalyzed transesterification in a non-aqueous biphasic medium. Vinyl caprate was mechanically dispersed into a solution of sucrose in DMSO. The use of DMSO allowed increasing sucrose concentration up to 0.7 M (in DMSO). The denaturing effect of DMSO on lipase was avoided by pretreatment of lipase by pH adjustment in the presence of crown ether. This pretreatment maintained a significant catalytic activity which led to 0.2 M sucrose monoester within 1 h at 50 °C, which represented higher productivity than already reported. Detailed structural characterization revealed that only monoester was recovered and the 2-O-acylated sucrose monocaprate was the major isomer in the final product.